Interlaboratory comparison of magnesium isotopic compositions of 12 felsic to ultramafic igneous rock standards analyzed by MC‐ICPMS. (25th September 2015) - Teng, Fang‐Zhen; Yin, Qing‐Zhu; Ullmann, Clemens V.; Chakrabarti, Ramananda; Pogge von Strandmann, Philip A. E.; Yang, Wei; Li, Wang‐Ye; Ke, Shan; Sedaghatpour, Fatemeh; Wimpenny, Joshua; Meixner, Anette; Romer, Rolf L.; et al.
Abstract To evaluate the interlaboratory mass bias for high‐precision stable Mg isotopic analysis of natural materials, a suite of silicate standards ranging in composition from felsic to ultramafic were analyzed in five laboratories by using three types of multicollector inductively coupled plasma mass spectrometer (MC‐ICPMS). Magnesium isotopic compositions from all labs are in agreement for most rocks within quoted uncertainties but are significantly (up to 0.3‰ in 26Mg/24Mg, >4 times of uncertainties) different for some mafic samples. The interlaboratory mass bias does not correlate with matrix element/Mg ratios, and the mechanism for producing it is uncertain but very likely arises from column chemistry. Our results suggest that standards with different matrices are needed to calibrate the efficiency of column chemistry and caution should be taken when dealing with samples with complicated matrices. Well‐calibrated standards with matrix elements matching samples should be used to reduce the interlaboratory mass bias.